1995
DOI: 10.1016/0014-5793(95)00203-l
|View full text |Cite
|
Sign up to set email alerts
|

Domain interactions stabilize the alternatively folded state of an antibody Fab fragment

Abstract: The structure of the Fab fragment of the monoclonal antibody MAK 33 (MIgG1) at pH 2 was characterized. Spectroscopic and kinetic analysis revealed a molten globule-like state, characterized by elements of secondary structure but less defined tertiary contacts than in the native state. However, some aromatic side chains are in an asymmetrical environment. This structure was not detected using the isolated light chain or a Fab fragment lacking the covalent linkage of the light chain and Fd via the C-terminal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 17 publications
6
33
1
Order By: Relevance
“…Their near-UV CD spectra ( Fig. 1c) with a minimum at 275 nm confirmed that the tertiary structure of both proteins is correctly formed (30,31). The presence of a buried tryptophan in close proximity to the disulfide in antibody domains makes it a sensitive probe for studying conformational changes by fluorescence.…”
Section: Biophysical Characteristics Stability and Amyloidogenic Prmentioning
confidence: 75%
“…Their near-UV CD spectra ( Fig. 1c) with a minimum at 275 nm confirmed that the tertiary structure of both proteins is correctly formed (30,31). The presence of a buried tryptophan in close proximity to the disulfide in antibody domains makes it a sensitive probe for studying conformational changes by fluorescence.…”
Section: Biophysical Characteristics Stability and Amyloidogenic Prmentioning
confidence: 75%
“…1b). 46,47 The domain contains two tryptophan residues at positions 35 and 94 (numbering adapted from the Kabat Database 48 ): the former is buried in close proximity to the disulfide, and the latter is found in a solvent-exposed position in CDR3. The presence of a buried tryptophan makes a sensitive probe for studying the conformation of the molecule by fluorescence, as shown by the spectra in Fig.…”
Section: Structural Characterisation Of V Lmentioning
confidence: 99%
“…Furthermore, the AFS often possesses a defined quaternary structure and, most importantly, it usually shows a rather high stability and cooperative unfolding transitions. [13][14][15] A species in between the molten globule and the AFS structure is the so-called acid state (A-state), which has been reported for a large number of proteins and is thought to form under acidic conditions if the charge repulsion of the protonated side chains is compensated for by the presence of anions. 2,16,17 In contrast to the AFS, its structure is often native like but only marginally stable, 18,19 but it does not adopt the globular shape that is a prerequisite for molten globule structures.…”
Section: Introductionmentioning
confidence: 99%